First Aid for the Psychiatry Clerkship - Ganti, L. Latha (McGraw-Hill Education, 2016)
Excel on rotation, impress on the wards, and score your highest on the psychiatry clerkship and shelf exams with this bestselling student-to-student review. Benefit from the wisdom of experienced clerkship faculty and residents. Mini-cases highlight classic patient presentations and frequently tested cases. A complete chapter on How to Succeed on the Psychiatry Clerkship provides a blueprint for exam success. Mnemonics, ward tips, mini-cases, diagrams, tables, and more provide a clear, realistic look at what to expect on exam day. Strong clinical emphasis guides you in the diagnosis and treatment of many problems seen by psychiatrists. Highlights all the important topics and provides a clear, concise review of psychiatry. Valuable discussion of medications and side effects. Everything you need to understand the differential diagnosis.